Cost-effectiveness of skin-barrier-enhancing emollients among preterm infants in Bangladesh - Amnesty LeFevre; Samuel D Shillcutt; Samir K Saha; ASM Nawshad Uddin Ahmed; Saifuddin Ahmed; MAK Azad Chowdhury; Paul A Law; Robert Black; Mathuram Santosham; Gary L Darmstadt (Bulletin of the World Health Organization)
OBJECTIVE: To evaluate the cost-effectiveness of topical emollients, sunflower seed oil (SSO) and synthetic Aquaphor, versus no treatment, in preventing mortality among hospitalized preterm infants (< 33 weeks gestation) at a tertiary hospital in Bangladesh. METHODS: Evidence from a randomized controlled efficacy trial was evaluated using standard Monte Carlo simulation. Programme costs were obtained from a retrospective review of activities. Patient costs were collected from patient records. Health outcomes were calculated as deaths averted and discounted years of life lost (YLLs) averted. Results were deemed cost-effective if they fell below a ceiling ratio based on the per capita gross national income of Bangladesh (United States dollars, US$ 470). FINDINGS: Aquaphor and SSO were both highly cost-effective relative to control, reducing neonatal mortality by 26% and 32%, respectively. SSO cost US$ 61 per death averted and US$ 2.15 per YLL averted (I$6.39, international dollars, per YLL averted). Aquaphor cost US$ 162 per death averted and US$ 5.74 per YLL averted (I$ 17.09 per YLL averted). Results were robust to sensitivity analysis. Aquaphor was cost-effective relative to SSO with 77% certainty: it cost an incremental US$ 26 more per patient treated, but averted 1.25 YLLs (US$ 20.74 per YLL averted). CONCLUSION: Topical therapy with SSO or Aquaphor was highly cost-effective in reducing deaths from infection among the preterm neonates studied. The choice of emollient should be made taking into account budgetary limitations and ease of supply. Further research is warranted on additional locally available emollients, use of emollients in community-based settings and generalizability to other geographic regions.